Treatment with Medical Ozone Therapy via Vaginal Insufflation in a Mexican female patient infected with HPV 16,18. Case report (Ozone Therapy Global Journal, 2017)
Uterine-cervix cancer is the 4th cancer worldwide with high rate of mortality and incidence, it’s been proposed several treatments as chemotherapy, radiotherapy among others. Medical ozonetherapy it has been used in gynecology in inflammatory and chronical infectious process due to inmunoestimulatory ability, induction of antioxidant enzymes and the bactericide and virucide properties. We present a medical case of a Mexican patient diagnosed of High degree intraepithelial lesion by 16 and 18 HPV. She received vaginal influx of medical ozonetherapy (20 sessions). After the medical ozone treatment, it was report by colposcopy and qPCR no HPV infection and no cervical inflammatory or transformation changes. Remission of the epithelial changes and the no presence of HPV could response to the effects in blood circulation of the medical ozonetherapy as peroxidation, angiogenesis, upregulation of immune system ( Tumor necrosis factor, interleukina 2, interpheron), presence of peroxidase gluthathion, catalase, dismutase superoxide and the vaginal effects as intreleukine -6 and myeloperoxidase. We conclude it is necessary further and deeper investigation of the effect in HPV infections of medical ozone-therapy, nevertheless we could find a positive correlation between treatment and remission of the HPV infection process and their structural changes